Scotland as we know it representations of national identity in literature, film, and popular culture - Zumkhawala-Cook, Richard (McFarland, 2008)
"Popular representations of Scottish national, ethnic, and cultural identity are in abundance not only in Scotland, but also in the United States, Canada, and throughout the Anglophone settler nations of the world. Scotland, then, in its cultural presence as a "nation without a state," serves as a fitting site for a study of nationality in the modern world"--Provided by publisher.
Includes bibliographical references and index
Keywords: Geschichte; Nationalismus; National characteristics, Scottish; Nationalism -- Scotland -- History; Nationalbewusstsein; Volkskultur; Schottland; Scotland -- In popular culture; Scotland -- In motion pictures; Scotland -- Historiography